Effect of porogen solvent on the properties of nickel ion imprinted polymer materials prepared by inverse suspension polymerization. (February 2017) - Meouche, Walid; Laatikainen, Katri; Margaillan, André; Silvonen, Timka; Siren, Heli; Sainio, Tuomo; Beurroies, Isabelle; Denoyel, Renaud; Branger, Catherine
Graphical abstract: Highlights: Nickel ion-imprinted polymers were prepared by inverse suspension polymerization. Acetonitrile and 2-methoxyethanol were added to DMSO as coporogen solvents. Binding properties depend on the ligand-metal complex stabilization by the solvent. The polymethacrylate backbone weakly interacts with nickel. The imprinting effect was evidenced by comparison with a commercial resin. Abstract: Ion-imprinted polymers (IIPs) for nickel were synthesized by inverse suspension copolymerization of vinylbenzyl iminodiacetic acid (VbIDA) with ethyleneglycol dimethacrylate (EDMA) in the presence of nickel(II) ions with various porogen solvents to study their impact on the IIPs properties. They were prepared with mixtures of acetonitrile and dimethylsulfoxide (DMSO), 50/50%v/v, for IIP-A/D and 2-methoxyethanol and DMSO, 50/50%v/v, for IIP-M/D. The structure and properties of these polymers were compared with those of IIP-D previously prepared with pure DMSO as porogen solvent. Although IIP-A/D and IIP-M/D were less porous than IIP-D, they presented better nickel adsorption properties and selectivity towards Zn 2+, Co 2+ and Pb 2+ . This is assumed to be the result of the stabilization of the ligand-metal complex during the polymerization process. Moreover, the nickel binding capacities of the prepared IIPs in competitive conditions are remarkably high (184 μmol/g for IIP-D, 170 μmol/g for IIP-A/D and 174 μmol/g for IIP-M/D). The impact of the VbIDA chelating monomer was highlighted by comparing the adsorption properties of a copolymer of methyl methacrylate (MMA) and EDMA with NIP-D. It was proved that the methacrylic polymer matrix has low binding properties.